2016 ESC GUIDELINES FOR THE MANAGEMENT OF ATRIAL FIBRILLATION DEVELOPEDIN COLLABORATION WITH EACTS - Paulus Kirchhof; Stefano Benussi; Dipak Kotecha; Anders Ahlsson; Dan Atar; Barbara Casadei; Manuel Castella; Hans-Christoph Diener; Hein Heidbuchel; Jeroen Hendriks; Gerhard Hindricks; Antonis S. Manolis; et al. (Российский кардиологический журнал)
The Task Force for the management of atrial fibrillation of the European Society of Cardiology (ESC)Developed with the special contribution of the European Heart Rhythm Association (EHRA) of the ESCEndorsed by the European Stroke Organisation (ESO)